(untitled) (REMUNOM, 2026)
The process of writing the Undergraduate Thesis (Final Course Project) has often been associated with high levels of stress, anxiety, and psychological distress among university students. In this context, this study aimed to identify the factors related to students’ mental distress during the development of their thesis, as well as to analyze how these experiences are expressed on a social network. This is a qualitative study with a netnographic approach, based on the collection of comments (tweets) published on Twitter. Initially, a bibliographic review was conducted in scientific databases, followed by the collection of 69 tweets using keywords related to the topic, of which 28 were selected for analysis. The data were examined using Content Analysis, according to Bardin, allowing the organization into three thematic categories: interpersonal relationships in the academic environment, external factors to university life, and aspects related to the writing process, such as fluency and procrastination. The results indicate that students’ psychological distress is associated not only with the academic demands of the thesis but also with external factors, such as socioeconomic conditions, family relationships, and workload. Furthermore, positive relationships with advisors and affinity with the chosen topic contribute to a less distressing experience. It is concluded that the thesis writing process, although challenging, can be less harmful to mental health when there is institutional support, healthy academic relationships, and better coping conditions among students. The study highlights the need for further research and strategies aimed at promoting mental health in the university context.